Pengaruh Internet Terhadap Akhlak Siswa Kelas XI MAN 1 Tanah Bumbu - Mudasir Mudasir (UM Purwokerto Press, 2022)
This study aims to obtain an overview resulting from the influence of internet use on the morals of class XI students at MAN 1 Tanah Bumbu. The data from this study were obtained from the results of interviews, observations, and documentation. The data analysis of this research used descriptive qualitative method, which consisted of data analysis as well as data reduction, data presentation and conclusions. The results of this study conclude that the internet has an effect on the morals of class XI students at MAN 1 Tanah Bumbu. The effects resulting from the use of the internet on students' morals include; (1) less enthusiastic or lazy in learning to understand the subject matter through the teacher's explanation, because students find it quite easy to get answers via the internet, (2) students feel impolite to their teachers, feel that the knowledge they get is not from the teacher but their own efforts as search results on the internet, (3) students are influenced to imitate bad things from spectacles obtained through the internet, pornographic videos, fights, and other bad things that cause morals to become.